Nature meets nurture : science-based strategies for raising resilient kids - Doan, Stacey N.; Borelli, Jessica L. (American Psychological Association, 2022)
"Every parent has pondered "nature vs. nurture" questions. How much of my child's personality and behavior is inborn? How much is learned? This important new book written by behavioral scientists who are also mothers has answers. This book offers the best parenting practices to foster resilience by encouraging children's social-emotional development and adaptive stress-regulation strategies. The authors translate scientific research into concrete, actionable tips and recommendations to help promote the emotional wellbeing of both child and parent. Authors Stacey N. Doan and Jessica Borelli offer a science-based framework to help show parents and guardians how biology and parenting work together. Although genetics are significant, DNA is not destiny--the die is not cast at birth. Parenting still matters, deeply. Cutting-edge epigenetics research and other recent scientific insights are explained to show that biology and parenting behavior are integrally intertwined. Increasingly competitive schools, looming threats of climate change, and the Covid-19 pandemic have sent many parents' anxiety spiraling out of control. This affects their kids, creating a recurring cycle of stress and worry. This book is here to help. "--